Peran Fintech Syariah dalam Meningkatkan Akses Pembiayaan Bagi Generasi Milenial: Studi terhadap Persepsi, Tingkat Kepercayaan, dan Perilaku Keuangan Digital - Moh Farhan; Jailani Jailani (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2025)
The development of Islamic financial technology (Islamic fintech) has brought significant transformation to the Islamic financial system, particularly by offering more inclusive financing alternatives aligned with Sharia principles. Millennials, as a digitally savvy and economically active generation, have become the primary target for Islamic fintech services. However, challenges remain in terms of their level of trust and understanding of the mechanisms and contracts used in these services. This study aims to thoroughly analyze how millennials’ perceptions, trust levels, and digital financial behavior influence their access to financing through Islamic fintech platforms. This research employs a quantitative approach through a structured questionnaire survey involving 150 active users of Islamic fintech. Data were analyzed using multiple linear regression to examine the relationships between variables. The findings reveal that a positive perception regarding ease of use, Sharia compliance, and service transparency significantly increases millennials’ trust. This elevated trust then encourages more active digital financial behavior, which in turn enhances access to Islamic financing. The study offers valuable insights into the factors driving the adoption of Islamic fintech among the younger generation and provides recommendations for policymakers and service providers to focus on Sharia financial literacy, education on Islamic contracts, and the strengthening of Sharia-aligned digital features.